A Cross-Sectional Examination of 10-Year Atherosclerotic Cardiovascular Disease Risk Among US Firefighters by Age and Weight Status. Issue 12 (December 2020) - Hollerbach, Brittany S.; Mathias, Kevin C.; Stewart, Donald; Jack, Kepra; Smith, Denise L.
Abstract : Objective: Examine atherosclerotic cardiovascular disease (ASCVD) risk scores by age and weight status in career firefighters. Methods: Medical examinations for firefighters more than or equal to 40 years ( n  = 644) were examined. ASCVD 10-year risk scores were calculated from sex- and race-specific equations and were reported by three age (40 to 44.9, 45 to 49.9, more than or equal to 50 years) and weight (normal, overweight, obese) categories. Results: Mean risk scores were 1.8%, 3.5%, and 6.2% for firefighters 40 to 44.9, 45 to 49.9, and more than or equal to 50 years, respectively. The association of weight status with increased ASCVD risk was higher ( P  < 0.01) among older firefighters, where risk was 0.8% (95% confidence interval [CI]: 0.6 to 1.1) and 2.3% (95% CI: 2.0 to 2.6) among normal versus obese 40 to 44.9 year olds, and 4.1% (95% CI: 3.1 to 5.3) and 7.8% (95% CI: 6.7 to 8.9) among normal versus obese more than or equal to 50 year olds. Conclusions: While firefighters cannot avoid aging, physicians should counsel firefighters with weight-maintenance or weight-loss advice to prevent and manage elevated ASCVD risk. Abstract : Supplemental Digital Content is available in the text